Optimalisasi Manajemen Intervensi Kelas Terhadap Perilaku Buruk Siswa SD di Madrasah Ibtidaiyah - Novitasari, Noer Intan (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2017)
This study focused on examining the theory of optimalization of class intervention management toward students’ bad behavior in Islamic primary school. The method used in this study was literature study based on documents. The results showed that the optimalization of classroom management involved the whole components including school and parents as moral community whose responsibility and role were preventing and overcoming students’ bad behavior by being a good role model. Optimizing the collaboration among parents enables integrated communication with education at school to avoid the continuity of behavior. Increasing positive activities aimed to overcome disruption in the classroom can be done through behaviorism approach and integrated learning. Teachers’ readiness in mastering intervention management is crucial as it is necessary for dealing with students’ behavior in a precise way. Keywords: Class Intervention management, Bad Behavior, Islamic Primary School